1775 : a good year for revolution - Phillips, Kevin, 1940- (New York : Viking, 2012)
A noted historian and political commentator claims 1775 as the American Revolution's true beginning.
Includes bibliographical references (p. [593]-604) and index.
Keywords: Paine, Thomas, 1737-1809. -- Common sense; United States. -- Continental Congress; Lexington, Battle of, Lexington, Mass., 1775.; Concord, Battle of, Concord, Mass., 1775.; United States -- History -- Revolution, 1775-1783.